The Tri-Lift suspension technique: a modified deep-plane lip lift for enhanced aesthetic outcomes—my personal approach - Bayad Jaza Mahmood (Maxillofacial Plastic and Reconstructive Surgery)
Abstract Background The subnasal lip lift has emerged as a popular intervention for correcting an elongated upper lip, although postoperative scarring remains a topic of concern. Various techniques have been discussed in the literature, with the Tri-Lift suspension technique highlighted in this study offering to reduce such complications and to assess the impact of modification in the deep plane subnasal lip lift, which includes triple suspension sutures, on nasal and labial aesthetic parameters. Results A total of 193 female patients (mean age: 28 years) underwent the Tri-Lift suspension technique, while 50 female patients (mean age: 32.48 years) underwent the traditional lip lift (bullhorn technique). In the Tri-Lift group, 78.7% reported “very much improvement,” 20.2% “much improvement,” and 1% “no change,” compared to 43% “very much improvement,” 28.6% “much improvement,” 21.4% “improved,” and 7% “no change” in the traditional lip lift group. Quantitative measurements of philtral length, vermilion height, and dental show recorded preoperatively and 6 months postoperatively showed significant improvements in both groups. However, the Tri-Lift suspension technique achieved higher satisfaction rates, fewer adverse outcomes, and statistically significant differences in satisfaction levels (P < 0.05) compared with the traditional lip lift. Conclusions The Tri-Lift suspension technique offers a solution to the common issue of scarring in subnasal lip lifts, enhancing both nasal and lip aesthetics. It presents a promising alternative to the traditional method, providing higher patient satisfaction and better aesthetic outcomes with reduced scarring. Graphical abstract